Pengaruh Budaya Organisasi dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior (OCB) pada PT Amel Indah Abadi Indramayu - Aji Taufiq; Muhamad Alwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of organizational culture and organizational commitment on Organizational Citizenship Behavior (OCB) at PT Amel Indah Abadi Indramayu. The research employed a quantitative associative approach involving 73 respondents, representing all active employees of the company. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression with SPSS version 23. The results show that partially, organizational culture has no significant effect on OCB with a significance value of 0.722 (>0.05), and organizational commitment also has no significant effect on OCB with a significance value of 0.609 (>0.05). Simultaneously, organizational culture and organizational commitment do not significantly affect OCB with a significance value of 0.875 (>0.05). The coefficient of determination (R²) is 0.004, indicating that organizational culture and organizational commitment explain only 0.4% of the variance in OCB, while the remaining 99.6% is influenced by other factors outside this study. These findings indicate that employees’ Organizational Citizenship Behavior (OCB) is more influenced by other factors such as leadership, reward systems, job satisfaction, and organizational justice. Therefore, companies need to strengthen comprehensive human resource management strategies to enhance employee OCB.